Bad feminist: essays - Gay, Roxane (Harper Perennial, 2014)
In these funny and insightful essays, Gay takes us through the journey of her evolution as a woman (Sweet Valley High) of color (The Help) while also taking readers on a ride through culture of the last few years (Girls, Django in Chains) and commenting on the state of feminism today (abortion, Chris Brown). The portrait that emerges is not only one of an incredibly insightful woman continually growing to understand herself and our society, but also one of our culture.Bad Feminist is a sharp, funny, and spot-on look at the ways in which the culture we consume becomes who we are, and an inspiring call-to-arms of all the ways we still need to do better, coming from one of our most interesting and important cultural critics.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; cours; culture populaire; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis; études littéraires

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Le vertige des insectes: roman - Veilleux, Maude (Hamac, 2014)
« Le décès de sa grand-mère et le départ de son amoureuse pour le Yukon replongent Mathilde au coeur de souvenirs douloureux liés à la mort. Dans l'enceinte de son appartement, elle s'enlise lentement dans la complexité d'un quotidien aux contours sombres. Roman d'atmosphère, Le Vertige des insectes nous fait pénétrer dans un univers où illusion et divagation se collent au corps telle une seconde peau. »-- Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; arts; canada; cours; discipline; identités LGBTQIA2+; lesbianisme; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; yukon; écriture des femmes*; études littéraires